Evaluation of Patients’ Experience Following Dental Implant Surgical Procedure (2020)
Background: Patient’s acceptability of dental implant prostheses may be influenced by the fact that a surgical procedure is involved. Adequate relevant information by the dental professionals pre-surgery, is therefore, paramount to alleviating the fear of surgery and contribute positively to patient’s ability to cope with post-surgical experience. This study, therefore, aimed at evaluating the postsurgical experience of the dental implant patients as against what was expected, and relate this with the information given pre surgery. Methodology: Post treatment self-completed questionnaires were administered to consented patients that had dental implants placed between July 2017 and December 2019. The surgical procedure followed the standard protocol and data related to post-surgical experience were collected one week after the surgery to obtain information on the level of pain/discomfort and amount of swelling experienced following surgery. The effect of the information on coping ability following surgery was also assessed. Data were analyzed using descriptive statistics (p value ≤ 0.05). Results: Twenty-seven patients received 44 implants to replace 48 teeth. The mean age of the patients was 45 ± 16.3 (SD) years. Teeth mostly replaced were the maxillary central incisors (39.6%). The majority of the patients 77.7% reported to experience less pain/discomfort than expected and 66.6% had less swelling than expected. While 29.6% felt they had excellent explanation of what to expect, 51.9% said they had good explanation. The post-surgical experience between males and females was not statistically significant (pain: p = 0.08, swelling: p = 0.64). However, the majority (8/12) that had good to excellent information preoperatively, had significantly less discomfort than expected. Conclusion: Positive, encouraging and satisfactory experience of patients following implant surgical procedure is related to adequate and correct information pre-surgery. How